INFORMATION WARFARE AND PSYCHOLOGICAL THREATS IN OPEN INFORMATION ENVIRONMENTS - B. Umarov (American Journals Publishing, 2025)
In the context of rapid digital transformation and the formation of a global information society, information systems have become a decisive factor in social development, governance, and human interaction. At the same time, the growing volume, speed, and openness of information flows have generated new risks related to information and psychological security. This article examines the conceptual foundations of information processes, information systems, and information technologies, emphasizing their role in decision-making and state governance. Special attention is paid to automated information systems as human–machine complexes that support managerial activity and influence social stability. The study also analyzes the challenges of information security in highly informatized environments, highlighting the need for a modernized state information policy capable of countering information and psychological threats. The article argues that ensuring information and psychological security requires not only technical solutions but also socio-psychological, ethical, and ideological mechanisms aimed at protecting national interests, strengthening public trust, and fostering sustainable development in open information systems.
Keywords: Information systems; information technologies; information security; psychological security; automated information systems; state information policy; information society.